EVALUASI PROSES PENDATAAN PROGRAM JKN BPJS KESEHATAN DI DESA MERANTI KECAMATAN MERANTI KABUPATEN LANDAK - Widiawati E.21110041 (PublikA, Jurnal Ilmu Administrasi Negara, 2014)
The article entitled "Evaluation of the National Health Insurance Scheme Social Security Agency of Health" The writing of this article is intended to evaluate the data collection process of the National Insurance Scheme Keseahatan Social Security Agency in the Health District of Meranti Meranti village Porcupine District.The conclusion from these results is that the socialization provided by related parties to Meranti villagers about JKN BPJS Health program is still considered not optimal, considering that to date most of the people in the village Meranti there who do not know or are confused JKN BPJS Health related programs , as well as many poor people who have not been recorded as participants JKN BPJS Health, because at the time of data collection will be done msayarakat not notified in advance by the subdistrict and village data collection that would be poor to be a participant JKN BPJS Health. In the election of poor households experience a problem that is not on target, should the people who deserve the help of the program just does not get health insurance, even the people who actually do not deserve it get the help of the health insurance. At the time of field verification process and the people in the village aspiration Meranti is not done by those involved in the current recall until the officer did not pull back the card participants who are not the right target. And in the enumeration process of the data collection officer's house is not supervised by a team of Central Bureau of Statistics (BPS) so that officers of the village who did not record properly enumeration. Keyword :    JKN BPJS Health Program Evaluation, Beneficiary Contribution, Socialization Program, Program Recipients Networking, Data Validation and Enumeration Program Recipients.